Pengaruh Pendampingan Persalinan dan Pemberian Endorphin Massage oleh Keluarga terhadap Tingkat Nyeri Ibu Bersalin di Wilayah Jabodetabek - Rahmadhena, Melisa Putri; Sianipar, Agustina; Sembiring, Desi Afrilia (Universitas Malahayati, 2025)
ABSTRACT Background: Severe and untreated labor pain will be fatal to the mother, because it can affect the mother's condition of fatigue, fear, worry and cause stress. non-pharmacological therapy such as endorphin massage can provide calm. Purpose of Writing: To determine the effect of childbirth assistance and endorphin massage by families on the level of pain in mothers giving birth in the Jabodetabek area. Research Method: The type of quantitative analytical research is quasi-experimental or pseudo-experimental, the sample in this study was 80 people, paired t-test analysis test. Research Results : Respondents who experienced mild pain were 2 people (10%), respondents who experienced moderate pain were 8 people (40%), and respondents who experienced severe pain were 10 people (50%). Conclusion and Suggestions: Assistance and provision of endorphin massage by families have an effect on the level of labor pain p-value = (<0.05). It is hoped that the Health Center can provide counseling or education to mothers and mothers' companions during labor about the benefits of assistance and provision of endorphin massage which can reduce pain levels during labor Keywords: Childbirth, Endorphin Massage, Pain ABSTRAK Nyeri persalinan yang hebat dan tidak tertangani akan berakibat fatal kepada ibu, karena dapat mempengaruhi kondisi ibu kelelahan, rasa takut, khawatir hingga menimbulkan stress. terapi non farmakolgi seperti endorphin massage yang dapat memberikan ketenangan. Untuk Mengetahui Pengaruh Pendampingan Persalinan Dan Pemberian Endorphin Massage Oleh Keluarga Terhadap Tingkat Nyeri Ibu Bersalin Di Wilayah Jabodetabek. Jenis penelitian analitik kuantitatif quasi experiment atau eksperimen semu, sampel pada penelitian ini berjumlah 80 orang, uji analisis paired t test. Responden yang mengalami nyeri ringan sebanyak 2 orang (10%), responden yang mengalami nyeri sedang sebanyak 8 orang (40%), dan responden yang mengalami berat sebanyak 10 orang (50%). Pendampingan dan pemberian endorphin massage oleh keluarga memiki pengaruh terhadap tingkat nyeri persalinan p- value = (<0,05). Diharapkan Puskesmas dapat nelakukan penyulahan atau memberikan edukasi kepada para ibu dan pemdamping ibu saat persalinan tentang manfaat pendampingan dan pemberian endorphin massage yang dapat menurunkan tingkat nyeri saat persalinan. Kata Kunci: Persalinan, Endorphin Massage, Nyeri